The metropolitan century. Understanding urbanisation and its consequences. - (:unkn) unknown (My University, 2015)
The report provides an outline of recent and likely future urbanisation trends and discusses the consequences. The world is in the middle of an urbanisation process that will cause urbanisation rates to rise from low double digit rates to more than 80% by the end of the century. It argues that this is both a great opportunity and a great challenge, as decisions taken today will affect the lifes of people for a long time to come. The report aims at explaining why cities exist, and what can make them prosperous and function well. It also discusses whether cities are good for residents, for the countries they are located in and for the global environment. The report argues that cities exist and grow because they are a source of economic prosperity and offer amenities that benefit their residents. It concludes that urbanisation is a process that needs to be shaped by policy makers to ensure that all benefit from it.
Keywords: Stadtsoziologie; Stadtwachstum; Wirtschaftsentwicklung; Millionenstadt; Großstadt; Stadtgröße; Zukunft; Stadtsoziologie; Internationaler Vergleich; Städtevergleich; Urbanisierung; Reurbanisierung; Städtewachstum; Rahmenbedingung; Metropole; Stadtbewohner